Analysis of the Effect of Modification of the Semi-Mechanical Pericarp on The Quality of Nutmeg Seeds - Mizan Reski Arsandi; Hermanto Hermanto; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2021)
The purpose of this study was to determine the effect of the modified semi-mechanical nutmeg pulp breaker (pericarp) on the presentation of damage to the yield of split nutmeg seeds. This research was conducted in two stages, namely the stage of making the tool and testing the device. The testing stages are as follows: In the framework, there is a place to put the nutmeg to be split, the space is shaped like a rectangular box, inside the box, space can be filled with three nutmegs. So, every time the nutmeg is split process, there is three split nutmeg. The stages observed in this study are the percentage of yield damage, the nutmeg splitter's input capacity, the nutmeg splitter's adequate capacity, yield, and uniformity of cleavage data. The testing results of this tool resulted in a reasonable degree of 512 ±162,774 pieces/hour, yield damage of 9.9 ±15.940%, and yield of 90.1 ±15.940%. This tool is more efficient because it is easier to use and does not use motor power. The working capacity of this semi-mechanical splitter is doubled when compared to manual splitters